2007
DOI: 10.1038/sj.onc.1210223
|View full text |Cite
|
Sign up to set email alerts
|

In vivo regulation of p21 by the Kruppel-like factor 6 tumor-suppressor gene in mouse liver and human hepatocellular carcinoma

Abstract: Kruppel-like factor (KLF) 6 is a tumor-suppressor gene functionally inactivated by loss of heterozygosity, somatic mutation and/or alternative splicing that generates a dominant-negative splice form, KLF6-SV1. Wild-type KLF6 (wtKLF6) expression is decreased in many human malignancies, which correlates with reduced patient survival. Additionally, loss of the KLF6 locus in the absence of somatic mutation in the remaining allele occurs in a number of human cancers, raising the possibility that haploinsufficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 36 publications
3
69
1
1
Order By: Relevance
“…, reduction of roughly 80% in proliferating cell nuclear antigen expression and 50% decrease in DNA synthesis, consistent with reduced cell proliferation of hepatocytes from KLF6 transgenic mice (32). Additionally, there was a significant correlation between low levels of KLF6 and p21 CIP1/WAF1 mRNA expression in primary hepatocellular carcinoma, suggesting that decreased expression of p21 CIP1/WAF1 in primary tumors results, at least in part, from the downregulation of the KLF6 tumor-suppressor gene (32).…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 65%
See 2 more Smart Citations
“…, reduction of roughly 80% in proliferating cell nuclear antigen expression and 50% decrease in DNA synthesis, consistent with reduced cell proliferation of hepatocytes from KLF6 transgenic mice (32). Additionally, there was a significant correlation between low levels of KLF6 and p21 CIP1/WAF1 mRNA expression in primary hepatocellular carcinoma, suggesting that decreased expression of p21 CIP1/WAF1 in primary tumors results, at least in part, from the downregulation of the KLF6 tumor-suppressor gene (32).…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 65%
“…Additionally, there was a significant correlation between low levels of KLF6 and p21 CIP1/WAF1 mRNA expression in primary hepatocellular carcinoma, suggesting that decreased expression of p21 CIP1/WAF1 in primary tumors results, at least in part, from the downregulation of the KLF6 tumor-suppressor gene (32).…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 93%
See 1 more Smart Citation
“…They suggested that only the first and third mechanisms would be involved. Recent reports by Narla et al 7 support the notion that the loss of one KLF6 allele, even in the absence of somatic mutations in the remaining one, could be enough to contribute to cell proliferation and tumor development. The exact mechanism by which this would be effective is still unknown.…”
Section: Discussionmentioning
confidence: 89%
“…6 This has been proven in several in vitro 5 and in vivo assays. 7 KLF6 is believed to regulate cancer development and progression through the downregulation of the c-Jun oncoprotein 8 and the activation of E-cadherin. 9 The reported frequency of KLF6 mutations in different types of human cancer varies in the different published studies.…”
mentioning
confidence: 99%